Properties of mixed cationic membranes studied by fluorescence solvent relaxation - Olżyńska, Agnieszka; Jurkiewicz, Piotr; Hof, Martin (Journal of fluorescence, 2008)
The need for detailed biophysical description of cationic lipid membranes, which are commonly used as gene transfection vectors, led us to study the properties of mixed cationic/zwitterionic lipid bilayers. Fluorescence solvent relaxation measurements of 6-dodecanoyl-2-dimethylaminonaphthalene (Laurdan) incorporated in a membrane consisting of cationic dimyristoyltrimethylammoniumpropane (DMTAP) and zwitterionic dimyristoylphosphatidylcholine (DMPC) were performed. The obtained results are compared with a recently measured system consisting of dioleoyltrimethylammoniumpropane (DOTAP) and dioleoylphosphatidylcholine (DOPC) (Jurkiewicz et al. Langmuir 22:8741-8749, 2006). The similar nonmonotonic dependence of the relaxation kinetics on cationic lipid content in the membrane was present for both systems. While the slowest solvent relaxation have been observed for 30 mol% of DOTAP in the DOPC bilayer (Jurkiewicz et al. Langmuir 22:8741-8749, 2006), for DMPC/DMTAP system it was found at 45 mol% of DMTAP, which agrees with the literature. Both membranes increased their hydration upon increased cationic lipid content.
Keywords: lipidy; Lipids; myristáty; membrány; laurany; kationty; 2-Naphthylamine; rozpouštědla; Dimyristoylphosphatidylcholine; fluorescenční barviva; fluorescence; Molecular Structure; Membranes; Lipid Bilayers; 2-naftylamin; kvartérní amoniové sloučeniny; Fluorescence; Quaternary Ammonium Compounds; molekulární struktura; Fluorescent Dyes; Financing, Organized; dimyristoylfosfatidylcholin; financování organizované; Laurates; Cations; lipidové dvojvrstvy; voda; Myristates; Solvents; Water